Ilmu Ladunni Dalam Perspektif Pendidikan Islam; Telaah Atas Pemikiran Abu Hamid Al-Ghazali - Yulianto - (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2017)
As a knowledge that is derived from eternal ray of light (TranscendentalGod) into majazi light (with different potentials) included in four humanâ€™sspirituality: mind, soul, spirit, and heart, Ladunni is an the innate and internal part ofhuman being that wait to be re-actualized. Therefore, the right perspective about thebirth of Ladunni is it becomes real because of the humanâ€™s effort and emanation ofGodâ€™s gift. Since the mediator of Ladunni actually has been stored in variouspotentials that belong to human beings since they were born, the role of education isto activate those innate abilities from potentials into the real humanâ€™s identity. Anactualization of humanâ€™s potential which is systematized in the learning process iscalled as humanistic curriculum. The objectives of this research were (1) determiningthe essence of Ladunni, (2) determining the method that was offered by Abu Hamidal-Ghazali to obtain the knowledge of Ladunni, and (3) determining the contributionof the knowledge of Ladunni towards Islamic education. This research was a libraryresearch with qualitative-descriptive approach. It used documentation as the datacollection, and content analysis to explore various data from the books written byAbu Hamid al-Ghazali which were then composed into systematic narration. Theresult of this research are (1) Ladunni is a product of actualization from varioushumanâ€™s potential which has been integrated in humanâ€™s spirituality; (2) everybodyis able to obtain the knowledge of Ladunni; (3) two methods which are used to obtainthe knowledge of Ladunni are internal and external methods. The coverage ofinternal method is learning, thinking, riyÄá¸atun nafsi, mujÄhadah also being patient,and the external method is by consuming halal food; (4) the access of Ladunni is alsodivided into external and internal, where external access is mirrored through aknowledge access called as divine revelation and divine inspiration while internalaccess can be seen from humanâ€™s spirituality; (5) humanistic curriculum is the mostsuitable curriculum in formal education to reflect the knowledge of Ladunni.Keyword: Ladunni in the Perspective of Islamic Education